Comparison of the effects of three types of aminobutyric acids on the control of Penicillium expansum infection in pear fruit. (4th August 2016) - Fu, Da; Sun, Yu; Yu, Chen; Zheng, Xiaodong; Yu, Ting; Lu, Huangping
Abstract: BACKGROUND: Aminobutyric acids were reported to have inhibitory effects on postharvest fungal diseases. The effects of α‐aminobutyric acid (AABA), β‐aminobutyric acid (BABA) and γ‐aminobutyric acid (GABA) on the control of Penicillium expansum infection in pear fruit were compared in the present study. RESULTS: BABA and GABA reduced the disease incidence of P. expansum infection in pear fruit when applied at an appropriate concentration and with a suitable treatment time. The efficacy of GABA was superior to BABA, whereas AABA had no inhibition effect. Three types of aminobutyric acids almost had no direct antifungal activity against P. expansum in vitro and in vivo, although BABA and GABA inhibited spore germination of P. expansum in vivo at a concentration of 100 mg L −1 when P. expansum was inoculated 24 h after treatment. Moreover, BABA and GABA enhanced catalase activity and all three aminobutyric acids enhanced peroxidase activity in pear fruit after being challenged by P. expansum, although BABA and GABA were more forceful than AABA. CONCLUSION: The position of the amino group in aminobutyric acids may be associated with the effects of aminobutyric acids on the control of postharvest fungal diseases. © 2016 Society of Chemical Industry